Study on silver nanoparticles as a novel explant disinfectant for micropropagation of African violet (Saintpaulia ionantha H. Wendl.) - Nhựt, Dương Tấn; Trinh, Dương Bảo; Cường, Đỗ Mạnh; Tùng, Hoàng Thanh; Huy, Nguyễn Phúc; Hiền, Vũ Thị; Luận, Vũ Quốc; Thu Hiền, Lê Thị; Châu, Nguyễn Hoài (Vietnam Journal of Biotechnology, 2018)
Surface sterilization is one of the most important steps in preparation of explants for micropropagation, because microbial contaminations present a major challenge to the initiation and maintenance of viable in vitro cultures. Most of popular surface disinfectants are considered as highly toxic influence either directly or indirectly to health and environment. Previous studies have demonstrated that toxicity of nano silver (Ag nanoparticles) can destroy effectively microorganisms but it is safe for human health. So, the silver nanoparticles have been widely used in different fields of life, such as medicine, pharmaceuticals, cosmetics, biology and agriculture. However, reports on the effect of silver nanoparticles for surface sterilization of plant explants are still limited. Nano silver and typical disinfectants were tested for sterilization of African violet (Saintpaulia ionantha H. WENDL.), by varying their concentration and time of exposure. The aim of this study was to examine sterilization capacity and explant morphogenesis when using nano silver in micropropagation. After decontamination step, we evaluated the growth and development of explants in different stages of the micropropagation process of African violet. The results indicated that the treatment using nano silver agent at concentration of 0.05% for 15 minutes was the best for controlling the infection. Nano silver could be used to replace the commonly used decontamination substances without causing adverse effects on plant growth and development. This is the first report on in vitro establishment using nano silver to reduce bacterial infections and the growth and development of African violet (Saintpaulia ionantha H. WENDL.).